Laporan Kasus: Pendekatan Multidisiplin dalam Manajemen Ketuban Pecah Dini pada Kehamilan Kembar - Rahmatullah, Muhammad Rayza; Sagia, Nabilla Alsa; Zahra, Tsurayya Fathma; Zulfadli, Zulfadli (Medula, 2024)
Twin pregnancies are high-risk conditions often accompanied by various complications, one of which is premature rupture of membranes (PROM). PROM is the rupture of the amniotic membrane before the onset of labor, occurring either before 37 weeks of gestation (preterm) or after (term). PROM significantly contributes to preterm births, a leading cause of global neonatal mortality. In Indonesia, the incidence of PROM increased from 13.1% in 2020 to 14.6% in 2021. This case study reports on a 36-week pregnant woman with twins who experienced PROM and successfully delivered vaginally with favorable outcomes for both the mother and neonates. The diagnosis of PROM was confirmed through anamnesis, physical examination, and supporting tests. Management included intensive observation, intravenous fluid administration, antibiotics, and antenatal steroids for fetal lung maturation. Previous research indicates that twin pregnancies significantly increase the risk of PROM. Key risk factors for PROM include a history of PROM, short cervical length, and low socio-economic status. Management of PROM in twin pregnancies involves the administration of antenatal steroids, latency antibiotics, magnesium sulfate for neuroprotection, and rigorous clinical and ultrasonographic monitoring. Diagnosis is performed via speculum examination and immunochromatographic tests. In conclusion, appropriate and effective management of PROM in twin pregnancies is crucial for improving pregnancy outcomes and reducing the risk of complications for both mother and infants.